Bridging Bangladesh and India : Cross-Border Trade and the Motor Vehicles Agreement - Herrera Dappe, Matias; Lebrand, Mathilde; Van Patten, Diana (World Bank, Washington, DC, 2021)
This paper studies the effects of removing transport and trade barriers between Bangladesh and India on aggregate real income and the distribution of population and real income within both countries. The paper uses a spatial general equilibrium model calibrated to these two economies, along with road network travel time calculated using GPS data, to measure changes in economic outcomes given changes in trade costs across regions. The paper focuses on the Motor Vehicles Agreement between Bangladesh, Bhutan, India, and Nepal and full transport and trade integration between Bangladesh and India. The counterfactual exercises show that decreasing transport and trade barriers between Bangladesh and India can lead to up to a 7.6 percent increase in national real income for India and a 16.6 percent increase for Bangladesh.